До передісторії Харківського університету. Федір Кудрицький – освітній діяч кінця XVIII – початку ХІХ ст. - Маслійчук, В. (Краєзнавство, 2016)
У статті висвітлюється дані біографії та особливості діяльності директора Харківського
головного казенного училища (згодом першого директора Слобідсько-Української гімназії), директора училищ Слобідсько-Української губернії 1798–1809 рр. Федора Кудрицького (1753 – після 1809). Відтворюються дані про навчання та кар'єру, проблематика освіти та освітніх
ініціатив у Харкові та Слобідсько-Українській губернії, передумови відкриття Харківського
університету. Розглядається історія Харківського головного казенного училища – провідного
світського навчального закладу в регіоні до відкриття університету. В статье исследуются биографические данные и особенности деятельности директора
Харьковского главного казенного училища (а потом и первого директора Слободско-Украинской
гимназии), директора училищ Слободско-Украинской губернии в 1798–1809 гг. Федора Кудрицкого (1753 – после 1809).
Воссоздаются подробности об учебе и карьере, проблематика образования и образовательных инициатив в Харькове и Слободско-Украинской губернии, обстоятельства открытия
Харьковского университета. Рассматривается история Харьковского главного казенного
училища – ведущего светского учебного заведения в регионе до открытия Харьковского университета. Secular education recognized became the traits of the modern world. The end of 18 – the beginning
of the 19 century is a very important time for the characteristics of the Secularization of education,
the emergence of new non-denominational schools. In this case, a very important will be the process
of transition, when the figure of the scholastic education is slowly becoming the main figure and
teacher in secular educational institutions. This article highlights biographie and feature of Fedir
Kudrycky the activity of the Kharkiv State school (then the first Director of the Slobodsko-Ukrainian
gymnasium), Director of schools slobodsko-Ukrainian province 1798–1809.
Fedir Kudrytsky was studied in Kharkiv Collegium (Orthodox educational institution). From 1771,
he began working in the secular educational institution of «additional classes», later converted to a
school.
Kudricky’s teacher’s career lasted until 1792, he became an Assistant Director and administrative
activities. From 1798 Kudrytsky became Director of schools Slobidsko-Ukrainian province. He managed
to establish the educational process and convert the Kharkov School of the leading educational
institution in the region. Thanks to successfully put learning school supplied včitel′s′kì frames as to
local institutions and schools in Central Russia. The success of the Kharkov school was recognized
by the State commissions and made a number of public finance. Kudrycky has made certain efforts to
play provincial schools, liquidated during 1797–1799. Thanks to the participation of the school were
later discovered in the Valky (1802), Lebedyn (1806), Vovchansk (1806).
The opening of the University in Kharkiv in 1805 r. was associated with the presence here of powerful
institutions. The first university students picked up during exams at school. The new educational
reform changed and Kudrycky’s suites, 1805, he became the first Director of the Slobidsko-Ukrainian
gymnasium, having there the learning process. But in the gymnasium in 1806 was eliminated the class
of music. In 1809 r. Kudrytsky resigned.
Biography of Fedir Kudrycki – a vivid example in the "new intellectuals", a very peculiar process
when a person with spiritual rank with theological education at the Orthodox Collegium, become
leaders of educational reforms and the formation of secular education. The study of these figures is
very important and can lead to new discoveries in the field of Ukrainian education and culture.